2006
DOI: 10.1111/j.1365-313x.2006.02830.x
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of PtdIns3P dynamics in living plant cells

Abstract: SummaryTo investigate PtdIns3P localization and function in plants, a fluorescent PtdIns3P-specific biosensor (YFP2xFYVE) was created. On lipid dot blots it bound specifically and with high affinity to PtdIns3P. Transient expression in cowpea protoplasts labelled vacuolar membranes and highly motile structures undergoing fusion and fission. Stable expression in tobacco BY-2 cells labelled similar motile structures, but labelled vacuolar membranes hardly at all. YFP-2xFYVE fluorescence strongly co-localized wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
222
0
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(251 citation statements)
references
References 83 publications
20
222
0
9
Order By: Relevance
“…1a-d). Both changes were abolished by the PtdIns(3)-kinase inhibitor wortmannin, which impedes autophagosome formation 39 ( Fig. 1e,f).…”
Section: Resultsmentioning
confidence: 99%
“…1a-d). Both changes were abolished by the PtdIns(3)-kinase inhibitor wortmannin, which impedes autophagosome formation 39 ( Fig. 1e,f).…”
Section: Resultsmentioning
confidence: 99%
“…It is intriguing that the exocyst complexes move back and forth between the plasma membrane and the cytoplasm (Fendrych et al, 2010(Fendrych et al, , 2013. In addition, FM4-64 is observed at the cell plate as early as the IPA stage, and phosphatidylinositol-4-phosphate (originating from both the Golgi and the plasma membrane) is integrated into the growing cell plate (Vermeer et al, 2009), with the accumulation of YFP-2x-FYVE-positive endosomes at the periphery of the growing cell plate (Vermeer et al, 2006(Vermeer et al, , 2009.…”
Section: Discussionmentioning
confidence: 99%
“…PtdIns(3)P represents 2-15% of the total monophosphate PIPs (38). Using a chimeric YFP fused with a tandem dimer of the PtdIns(3)P-binding FYVE domain from the growth factor-regulated tyrosine kinase substrate, it has been demonstrated that PtdIns(3)P localizes in both endosomal/pre-vacuolar vesicles and vacuolar membranes (119). Indeed, PtdIns(3)P has been shown to participate in vacuolar trafficking in Arabidopsis (22) and Nicotiana (120).…”
Section: Discussionmentioning
confidence: 99%